Proceedings of the Working Conference on Advanced Visual Interfaces 2004
DOI: 10.1145/989863.989867
|View full text |Cite
|
Sign up to set email alerts
|

Display space usage and window management operation comparisons between single monitor and multiple monitor users

Abstract: The continuing trend toward greater processing power, larger storage, and in particular increased display surface by using multiple monitor supports increased multi-tasking by the computer user. The concomitant increase in desktop complexity has the potential to push the overhead of window management to frustrating and counterproductive new levels. It is difficult to adequately design for multiple monitor systems without understanding how multiple monitor users differ from, or are similar to, single monitor us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 15 publications
(9 reference statements)
2
80
1
2
Order By: Relevance
“…A previous study [1] found that the mean time between window switches is only 20.9 seconds and that users have more than eight windows open more than 78% of the time. It has also been reported that the average number of simultaneously opened windows increases with available display space: from four for single monitor users to up to 18 for users with multiple monitors [2].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study [1] found that the mean time between window switches is only 20.9 seconds and that users have more than eight windows open more than 78% of the time. It has also been reported that the average number of simultaneously opened windows increases with available display space: from four for single monitor users to up to 18 for users with multiple monitors [2].…”
Section: Introductionmentioning
confidence: 94%
“…Observations show that window switching activities were far more frequent than window creation, deletion, or geometry management. Hutchings et al [1] update these findings using automatic logs of 39 participants over a 3-week period. They report on how window management activities differ across single-and multi-monitor display use (in common with Grudin's earlier field study [6]) but their data also highlights important general characteristics of window management.…”
Section: Studies Of Window Usementioning
confidence: 99%
“…One prominent study is that of the Rooms system [8] (notably the design of the Rooms tool was motivated by field research [3] just as snip was motivated by field research [7,9,10,11]). The Rooms study demonstrated the utility of what are today referred to as virtual desktops.…”
Section: Related Workmentioning
confidence: 99%
“…windows not receiving input from the user) while interaction takes place in the active window [7,9,10]. Applications are typically designed with an active user in mind, with little or no attention paid to how people might use the information displayed by an application when the window is not active.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the use of multiple monitors have revealed that additional displays are often treated as a discrete place to view output, rather than being used to enlarge the user's active working area [6,7]. Additionally, secondary monitors are often used to monitor information in the periphery, providing "instant access to a resource in a known location in peripheral vision" [6].…”
Section: Introductionmentioning
confidence: 99%